THE INFLUENCE OF ENTREPRENEURSHIP EDUCATION AND INDUSTRIAL WORK PRACTICES ON STUDENTS' INTEREST IN ENTREPRENEURSHIP AT SMKN 2 KANDANGAN - Khafifah, Khafifah; Ratumbuysang, Monry Fraick Nicky Gillian; Atmono, Dwi (International Conference On Social Science Education, 2023)
This study aims to determine (1) the effect of entrepreneurship education on entrepreneurial interest. (2) influence the practice of industrial exposure to interest in entrepreneurship. (3) the influence of entrepreneurship education and the practice of contacting the entrepreneurship industry on interest in entrepreneurship. The research method uses ex post facto with a quantitative approach, the research sample uses purposive sampling, and the number of research samples is 270 class XII students of SMK Negeri 2 Kandangan who have taken the subject entrepreneurship education and have carried out practical activities subject to industry. Data collection techniques use observation. Questionnaires and documentation Testing the instrument using validity and reliability test data analysis techniques included prerequisite analysis tests which included normality tests, linearity tests, heteroscedasticity tests, multicollinearity tests, anacoccal tests, Hypothesis testing using multiple linear regression tests with a significance level of 5%. Based on the results of the study, the following conclusions can be drawn: 1) Entrepreneurship education variable (X1) with a high category of 24 (8.9%) students, medium 197 (75.2) students, and low 49 (18.1%) students. 2) Variable industrial work practices (X2) with high category 16 (5.9%), medium 205 (75.9%) students, and low 48 (17.8%). 3) Variable interest in entrepreneurship (Y) high category 21 (7.8%) students. Medium 240 (88.9%) students, low 7 (2.6) students.